1997
DOI: 10.1161/01.cir.95.3.588
|View full text |Cite
|
Sign up to set email alerts
|

Role of Superoxide in Angiotensin II–Induced but Not Catecholamine-Induced Hypertension

Abstract: Hypertension caused by chronically elevated angiotensin II is mediated in part by .O2-, likely via degradation of endothelium-derived NO. Increased vascular .O2- may contribute to vascular disease in high renin/angiotensin II states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
544
4
9

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 755 publications
(586 citation statements)
references
References 33 publications
29
544
4
9
Order By: Relevance
“…The observation that hyperglycaemia is required to detect angiotensin II-induced expression of VEGF in cultured smooth muscle cells [16] could also be related to the formation of radicals, because of an altered cellular redox state induced by hyperglycaemia. These in vitro observations agree closely with earlier in vivo observations in rat aorta, namely that infusion of angiotensin II increases the production of superoxide anions by activation of NADPH oxidase, an effect that could be blocked completely by losartan [29,30]. From these data on smooth muscle cells a sequence of events is suggested that connects cellular activation by angiotensin II via NADPH oxidase activation, superoxide production and HIF1a activation to the transcriptional activation of the VEGF gene.…”
Section: Discussionsupporting
confidence: 90%
“…The observation that hyperglycaemia is required to detect angiotensin II-induced expression of VEGF in cultured smooth muscle cells [16] could also be related to the formation of radicals, because of an altered cellular redox state induced by hyperglycaemia. These in vitro observations agree closely with earlier in vivo observations in rat aorta, namely that infusion of angiotensin II increases the production of superoxide anions by activation of NADPH oxidase, an effect that could be blocked completely by losartan [29,30]. From these data on smooth muscle cells a sequence of events is suggested that connects cellular activation by angiotensin II via NADPH oxidase activation, superoxide production and HIF1a activation to the transcriptional activation of the VEGF gene.…”
Section: Discussionsupporting
confidence: 90%
“…Prolonged infusion of Ang II activates NAD(P)H oxidase in blood vessels (1,2,10,12), where it increases expression of the p22 phox , Nox-1, and Nox-4 components in VSMC from conduit vessels (33-35) and p67 phox in vascular adventitial cells (36). Small resistance vessels express gp91 phox , which also is upregulated by Ang II (37), and p67 phox and xanthine oxidase, which are unaffected by HS intake (8).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also substantial oxidative stress in the tissues or blood vessels of rats with desoxycorticosterone acetate-salt hypertension in which the circulating renin-angiotensin-aldosterone system is suppressed profoundly (4,5) and in models of salt-sensitive hypertension (6,7) and in normal rats fed a high-salt diet (8). Oxidative stress in hypertension has been demonstrated by the increased production of markers, such on the lipid peroxidation products isoprostanes (9) and malonyldialdehyde (MDA), and by BP lowering effects of cell-permeable forms of SOD (10) or its mimetics (9). O 2 ·Ϫ is produced in activated phagocytes by the enzyme NADPH oxidase (2,11).…”
mentioning
confidence: 99%
“…Accumulating evidence suggests that hypertension increases vascular production of reactive oxygen species, which can serve to oxidize BH 4 and lead to eNOS uncoupling. 9,10 Our previous experimental studies have shown that BH 4 is oxidized to dihydrobiopterin in the vasculature of the deoxycorticosterone acetate salt hypertensive mouse, and supplementation with oral BH 4 can reduce BP and improve oxidative stress in this model. 11 Several studies have assessed the effects of BH 4 on endothelial function.…”
Section: Introductionmentioning
confidence: 99%